TREM2 is associated with advanced stages and inferior prognosis in oral squamous cell carcinoma - Struckmeier, Ann-Kristin; Radermacher, Anne; Fehrenz, Michael; Alansary, Dalia; Wartenberg, Philipp; Wagner, Mathias; Scheller, Anja; Heß, Jochen; Moratin, Julius; Freudlsperger, Christian; Hoffmann, Jürgen; Thurner, Lorenz; et al. (Cancers, 2022)
Triggering receptor expressed on myeloid cells 2 (TREM2) is suggested to hamper antitumor immune response in multiple cancers. However, the role of TREM2 in oral squamous cell carcinoma (OSCC) and its expression in tumor-associated macrophages (TAMs) are unknown. In this study, TREM2 expression was analyzed in the primary tumors and corresponding lymph-node metastases of OSCC patients via immunohistochemistry on tissue microarrays. Human peripheral blood mononuclear cells (PBMCs) and single-cell suspensions of tumor and healthy adjacent tissues were analyzed for the presence of TREM2+ macrophages and TAMs using flow cytometry. The serum levels of soluble TREM2 (sTREM2) were quantified using an enzyme-linked immunosorbent assay. High TREM2 expression was associated with advanced UICC stages (Spearman’s rank correlation (SRC), p = 0.04) and significantly reduced survival rates in primary tumors (multivariate Cox regression, progression-free survival: hazard ratio (HR) of 2.548, 95% confidence interval (CI) of 1.089-5.964, p = 0.028; overall survival: HR of 2.17, 95% CI of 1.021-4.613, p = 0.044). TREM2 expression was significantly increased in the PBMCs of OSCC patients in UICC stage IV compared with healthy controls (ANOVA, p < 0.05). The serum levels of sTREM2 were higher in advanced UICC stages, but they narrowly missed significance (SRC, p = 0.059). We demonstrated that TREM2 was multi-factorially associated with advanced stages and inferior prognosis in OSCC patients and that it could serve as a prognostic biomarker in OSCC patients. Targeting TREM2 has the potential to reshape the local and systemic immune landscape for the potential enhancement of patients’ prognosis.